Truss Model for Shear Strength of Structural Concrete Walls - Chandra, Jimmy (2018)
Numerous methods for calculating shear strengths of structural walls are available. However, due to the complexity of wall behaviors and possible loading combinations that they may be subjected to, it is quite challenging to derive a method that is reasonably simple but can accommodate various influencing parameters in order to acquire more accurate predictions of wall shear strengths. The authors had earlier tested a series of very-high-strength concrete wall specimens (fc′ = 100 MPa [14,500 psi]) to investigate the influence on shear strength of several parameters, such as: height-to-length ratios, shear (web) reinforcement ratios in the vertical and horizontal directions, as well as the presence of flanges (boundary elements). The conclusions of the authors’ experimental study in the light of other research results reported by other researchers will be summarized herein and will be used as a guide for deriving a proposed truss model. The proposed model is based on modern truss analogy principles (softened truss model, compression field theory) and it has been shown by comparing it with experimental results to be accurate and stable. The design and analysis procedure based on the proposed truss model will also represent an improvement over existing ACI and Eurocode design procedures.